Late vs. early intrauterine blood transfusion in fetal anemia: impact on maternal and neonatal outcomes - Cahen Peretz, Adva; Tsaitlin-Mor, Lilah; Leibner, Gideon; Cohen, Sarah M.; Amosi-Victor, Danielle; Haham, Nitsan; Shwartz, Tomer; Yanai, Nili; Porat, Shay; Yagel, Simcha; Valsky, Dan V. (Frontiers in Medicine, 2025)
IntroductionOptimal timing of final intrauterine transfusion (IUT) and delivery in fetal anemia remains controversial, balancing procedural risks against prematurity complications. Our objective is to evaluate the safety and effectiveness of extending IUT beyond 34 weeks gestation in appropriately selected cases.MethodsRetrospective cohort study comparing pregnancies receiving late IUT (≥34 weeks, n = 21) versus early IUT (<34 weeks, n = 31) at a single tertiary center (2005–2024). We analyzed 200 IUT procedures in 52 pregnancies. Late IUT was offered to stable cases without hydrops or previous significant complications. Primary outcomes included procedure-related complications and prematurity-related outcomes.ResultsLate IUT showed no increase in procedure-related complications (0% vs. 20.0%, p = 0.069). Mean gestational age at delivery was higher in the late IUT group (37.2 ± 1.06 vs. 34.1 ± 3.6 weeks, p < 0.001), with reduced emergency cesarean rates (19% vs. 45%), higher birth weights (2,960 ± 399 g vs. 2,350 ± 620 g, p < 0.001), and lower NICU admission rates (29% vs. 71%, p < 0.05). These benefits persisted after adjusting for maternal characteristics. Subgroup analysis of hemolytic disease cases showed similar improvements with additional benefits in neonatal outcomes.DiscussionExtending IUT beyond 34 weeks in selected cases is safe and associated with improved obstetric and neonatal outcomes, supporting reconsideration of traditional gestational age limits for IUT.